Combination of searches for invisible Higgs Boson decays with the ATLAS Experiment - Onofre, A. (2019)
Dark matter particles, if sufficiently light, may be produced in decays of the Higgs boson. This Letter presents a statistical combination of searches for H→invisible decays where H is produced according to the standard model via vector boson fusion, Z(ℓℓ)H, and W/Z(had)H, all performed with the ATLAS detector using 36.1  fb−1 of pp collisions at a center-of-mass energy of √s=13  TeV at the LHC. In combination with the results at √s=7 and 8 TeV, an exclusion limit on the H→invisible branching ratio of 0.26(0.17+0.07−0.05) at 95% confidence level is observed (expected).